Interactions Between the Gut Microbiota and the Host Innate Immune Response Against Pathogens - Cheng, Hong-Yu; Ning, Meng-Xia; Chen, De-Kun; Ma, Wen-Tao (Frontiers in Immunology, 2019)
The mammalian intestine is colonized by over a trillion microbes that comprise the “gut microbiota,” a microbial community which has co-evolved with the host to form a mutually beneficial relationship. Accumulating evidence indicates that the gut microbiota participates in immune system maturation and also plays a central role in host defense against pathogens. Here we review some of the mechanisms employed by the gut microbiota to boost the innate immune response against pathogens present on epithelial mucosal surfaces. Antimicrobial peptide secretion, inflammasome activation and induction of host IL-22, IL-17 and IL-10 production are the most commonly observed strategies employed by the gut microbiota for host anti-pathogen defense. Taken together, the body of evidence suggests that the host gut microbiota can elicit innate immunity against pathogens.